Filosofi Informasi Dalam Pemberdayaan Layanan Perpustakaan - Alam, Umar Falahul (Pustakaloka, 2014)
Abstract:Â  The existence of the library indicates information services.Â  TheÂ  serviceÂ  showsÂ  twoÂ  interrelatedÂ  variables: theÂ  providerÂ  onÂ  theÂ  oneÂ  handÂ  andÂ  consumersÂ  onÂ  theÂ  other. Because of relation between service provider and customer satisfaction, then the service should beÂ  increasedÂ  from time to time. Library services also needs to be improved. Increased libraryÂ  services mustÂ  beÂ  appropriatedÂ  byÂ  itâsÂ  responsibilityÂ  to supportÂ  education,Â  teaching,Â  researchÂ  andÂ  community service. There is no doubt, that the library plays an important role inÂ  theÂ  processÂ  ofÂ  educationÂ  andÂ  teaching. TheÂ  frstÂ  library becomesÂ  anÂ  intermediaryÂ  betweenÂ  theÂ  usersÂ  andÂ  their information needs. Second, the library can be an information providerÂ  onÂ  oneÂ  sideÂ  andÂ  can beÂ  consultedÂ  forÂ  the usersÂ  in their academic activities. Third, the library can be a teacher who teaches the users the skills and strategies in managing, utilizing, andÂ  creatingÂ  information. TheÂ  role ofÂ  theÂ  library likes this, is named empowerment of library services